Pengaruh Fenomena Korean Wave (K-Pop dan K-Drama) Terhadap Perilaku Konsumtif Penggemarnya Perspektif Islam - Banowati Azelia Putri Yuliawan; Ganjar Eka Subakti (JURNAL PENELITIAN KEISLAMAN, 2022)
Nowadays, many young people like K-Pop and K-Drama, two types of South Korean culture that are included in the type of Korean wave. Motivating songs, good vocals and dance choreography, interesting and unique storylines, and talents of singers and actors are a few reasons why K-Pop and K-Drama are loved by many people. Idols also often release merchandise that is their trademark so that fans can buy them. This is what can make fans grow excessive consumptive behavior which is not recommended in Islam. The method used for this research is descriptive quantitative with the aim of research to discuss the consumptive behavior of K-Pop and K-Drama fans due to the Korean wave phenomenon. The results showed that most of the respondents admitted that their behavior which often buying their idol’s merchandise was included in consumptive behavior.